2002
DOI: 10.5713/ajas.2002.1790
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lactobacillus acidophilus Isolated from Piglets and Chicken

Abstract: Lactic acid bacteria were isolated from piglets and chicken and characterized. Lactic acid bacteria showing resistance to low pH and bile, adhesion to intestinal epithelium cells, and the inhibition of Escherichia coli and Salmonella spp. were identified as Lactobacillus acidophilus. L. acidophilus PF01 survived for 2 h in MRS broth adjusted to pH 2. L. acidophilus CF07 was less resistant than L. acidophilus PF01 to pH 2, but survived at pH 2.5 for 2 h. Both of isolates were able to grow in MRS broth containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…Bae & Lee (2002) obtained a pH higher (5.7) than ours and identified Lactobacillus bulgaricus including antibacterial activity. Ahn et al (2002) reported very acidic pH (2.5) and identified Lactobacillus acidophilus which has activity against Salmonella spp, Salmonella enteritidis and Salmonella typhimurium. Kang et al (2004) note that Lactobacillus fermentum multiplies at pH 2 to 4.…”
Section: Discussionmentioning
confidence: 99%
“…Bae & Lee (2002) obtained a pH higher (5.7) than ours and identified Lactobacillus bulgaricus including antibacterial activity. Ahn et al (2002) reported very acidic pH (2.5) and identified Lactobacillus acidophilus which has activity against Salmonella spp, Salmonella enteritidis and Salmonella typhimurium. Kang et al (2004) note that Lactobacillus fermentum multiplies at pH 2 to 4.…”
Section: Discussionmentioning
confidence: 99%
“…The proper selection and balance of lactic acid bacteria used for starter culture is critical for the manufacture of fermented food products with their desirable texture and flavor (Sanders, 2000). LAB are commonly used in most probiotics preparations due to being the desirable members of the intestinal microflora and thus beneficially amend the balance of intestinal microflora, inhibit the growth of harmful bacteria, promote good digestion, boost immune function and increase resistance to infection (Ahn et al, 2002). A potential probiotic bacterium must qualify certain selection criteria such as acid and bile stability, antimicrobial production and antagonistic activity and should be preferably of human origin.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus johnsonii PF01, which was isolated from piglet feces, was previously identified as L. acidophilus (1). This strain adheres specifically to duodenal and jejunal epithelial cells in piglets and inhibits the growth of Escherichia coli K88 and Salmonella spp.…”
mentioning
confidence: 99%
“…This strain adheres specifically to duodenal and jejunal epithelial cells in piglets and inhibits the growth of Escherichia coli K88 and Salmonella spp. (1). In addition, the strain has high bile resistance in vitro through bile salt hydrolase (BSH) activity against tauroconjugated bile salts.…”
mentioning
confidence: 99%